ASSESSMENT OF PESTICIDE RESIDUES IN OPEN WATER SOURCES - Akhmedova Saodat Tashboltaevna; Ermatov Nizom Jumakulovich (Innovate Conferences, 2025)
In today's era of development, along with a sharp increase in the number of factories and enterprises, the daily increase in modern industrial zones, along with the creation of jobs, the waste they produce plays a significant role in polluting not only the atmospheric air, but also the water, soil and food products in the region. At the same time, the use of a number of pesticides in the production of agricultural products, protection against pests in various environmental conditions, and the prevention of pollution of open water sources with pesticides together with their environment is one of the urgent problems facing the employees of the Committee for Sanitary, Epidemiological, Peaceful and Public Health.